2021
DOI: 10.1044/2020_jslhr-20-00014
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Aid Uptake, Benefit, and Use: The Impact of Hearing, Cognition, and Personal Factors

Abstract: Purpose The purpose of this study was to explore the effects of hearing, cognition, and personal factors on hearing aid (HA) uptake, use, and benefit. Method Eighty-five older adults aged 60–80 years ( M = 70.23, SD = 5.17) participated in the study. Hearing was assessed using pure-tone audiometry and the Listening in Spatialised Noise–Sentences test. Cognition was measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 72 publications
0
23
2
Order By: Relevance
“… Öberg et al (2012) and Tahden et al (2018) found that people were more likely to own a hearing aid if they had better self-reported health. In contrast, Nixon et al (2021) and Sawyer et al (2020) found that people were more likely to take up hearing aids if they had poorer self-reported health. Two studies reported on comorbidities and their relationship with hearing aid uptake.…”
Section: Resultsmentioning
confidence: 88%
“… Öberg et al (2012) and Tahden et al (2018) found that people were more likely to own a hearing aid if they had better self-reported health. In contrast, Nixon et al (2021) and Sawyer et al (2020) found that people were more likely to take up hearing aids if they had poorer self-reported health. Two studies reported on comorbidities and their relationship with hearing aid uptake.…”
Section: Resultsmentioning
confidence: 88%
“…General health was also assessed given its predictive role for different steps of the HA uptake path (4,6). The belief that HA are associated with old age and infirmity is often a barrier to HA uptake and use (4), therefore attitude towards ageing was assessed as well.…”
Section: Participantsmentioning
confidence: 99%
“…A further important predictive feature for help-seeking is physical health. Literature suggests that individuals who report poor health are more prone to uptake a HA (6) in order to improve their well-being.…”
Section: Which Psychological-and Hearing-related Features Are Mostly ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Adults with better psychomotor function and poorer self-reported health status are more likely to adopt and use their hearing aids (Nixon et al, 2021). The subjective experience of hearing also influences help-seeking behavior; Humes & Dubno (2021) found that older adults who do not seek treatment for hearing loss tend to perceive less difficulty with applied to evaluate traditional audiology and achieve our goal of producing a tool to compare differences between service delivery models.…”
Section: Introductionmentioning
confidence: 99%